2008
DOI: 10.1111/j.1469-1809.2008.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Age of SERPINA1 Gene PI Z Mutation: Swedish and Latvian Population Analysis

Abstract: SummaryAlpha 1-antitrypsin (A1AT) deficiency, one of the most common inborn errors of metabolism in Caucasians, is characterized by a low serum concentration of A1AT and a high risk of pulmonary emphysema and liver disease. The allelic frequency for the most common protease inhibitor (PI) Z mutation in the SERPINA1 gene is 2-5% in Caucasians of European descent.The objective of our study was to estimate the PI Z mutation age using molecular analysis in Latvian and Swedish populations, which have the highest fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Nevertheless, the findings of this study seem to be in accordance with the reported S and Z frequency distribution worldwide,1223 and with the hypothesis that both deficiency alleles originate from Caucasians living in Europe at different historical times. It is believed that the Pi*Z mutation has a relatively recent origin in Caucasians living in northern Europe ~2,000 years or 66 generations ago (one generation =30 years),25 and it was spread into the rest of the continent through maritime and inland waterways, via Baltic countries. On the other hand, it has been proposed that the S variant emerged in the Iberian Peninsula 300–450 generations ago (ie, 10–15,000 years ago), and in the Franco-Cantabrian refuge area during the last glacial era, spreading from there by people who later repopulated Europe 26.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the findings of this study seem to be in accordance with the reported S and Z frequency distribution worldwide,1223 and with the hypothesis that both deficiency alleles originate from Caucasians living in Europe at different historical times. It is believed that the Pi*Z mutation has a relatively recent origin in Caucasians living in northern Europe ~2,000 years or 66 generations ago (one generation =30 years),25 and it was spread into the rest of the continent through maritime and inland waterways, via Baltic countries. On the other hand, it has been proposed that the S variant emerged in the Iberian Peninsula 300–450 generations ago (ie, 10–15,000 years ago), and in the Franco-Cantabrian refuge area during the last glacial era, spreading from there by people who later repopulated Europe 26.…”
Section: Discussionmentioning
confidence: 99%
“…The most common monogenic inborn errors of metabolism associated with liver disease are hereditary hemochromatosis, alpha-1 antitrypsin deficiency, Wilson's disease, and Gilbert's syndrome. These diseases have a particularly high frequency in Northern Europe and Latvia [2][3][4] . Hereditary hemochromatosis is characterized by excessive iron overload and is most commonly caused by HFE gene mutations [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the most common HFE mutation, C282Y, is 0.035 in Latvia and 0.026 Lithuania; however, the frequency of hereditary hemochromatosis is lower at 0.013 [5] . Alpha-1 antitrypsin deficiency is caused by the absence of the proteinase inhibitor alpha-1 antitrypsin, and affected patients develop liver disease and emphysema in the third or fourth decade of life [3] . Wilson's disease is a progressive autosomal recessive disorder of copper metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…One cluster, including Baltic countries, Poland, and western Russia, has been described, and there are other reports of variants arising from, or being specific to, this region, for example, the Landsteiner Wiener blood (LWb) group, and the PI Z allele in the SERPINA1 gene, among others [14,15] . The first indicator of Baltic genetic influence described was the rs77493670 variant in the ICAM4 gene, also known as the LWb allele [16] .…”
Section: Discussionmentioning
confidence: 99%